Tingkat Pengetahuan Tentang Diet Pada Penderita Diabetes Mellitus di Salah Satu Rumah Sakit Swasta Yogyakarta - Larasati, Angelita Divana; Clarta, Anjalica Margareta; Dwi Antara Nugraha (Jurnal Indonesia Sehat, 2023)
Background:  Adherence to a diabetes diet in diabetes mellitus sufferers has a very important function, namely maintaining normal body weight, reducing blood glucose levels, improving lipid profiles, and increasing insulin receptor sensitivity. Apart from that, a good level of knowledge allows patients to be able to control themselves in overcoming the problems they face and comply with everything that has been recommended by health workers, such as the diet that has been determined by diabetes mellitus sufferers. These two things were the background for conducting research on the level of knowledge of diabetes diet in one of the private hospitals in Yogyakarta. Objective: . The research was carried out at the Internal Medicine Polyclinic in a private hospital in Yogyakarta with a total of 30 respondents. Methodology:  The research design in this study is a descriptive quantitative survey. Results:  The characteristics of respondents based on gender are dominated by female with 17 respondents (57%), the characteristics of respondents based on age are dominated by those over 50 years old, namely 27 respondents (90%), the characteristics of respondents based on education level, most respondents are high school graduates with 13 respondents (43.3%). Regarding the level of knowledge, the level of knowledge about the amount of food consumed by diabetes patients is dominated by respondents with sufficient qualifications, namely 13 respondents (43.3%), the level of knowledge about types of food, good qualifications is dominant with 23 respondents (76.7%) and the level of knowledge regarding eating schedules turned out to be 17 respondents (56.7%) with sufficient qualifications. Conclusion:  Based on research that has been conducted, the characteristics of respondents and the level of knowledge regarding diabetes diet are two factors that need attention in the management of patients with diabetes mellitus.